2021
DOI: 10.2196/32093
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Apps Leveraged in the COVID-19 Pandemic in East and South-East Asia: Review and Content Analysis

Abstract: Background The COVID-19 pandemic increased attention to digital tools to support governmental public health policies in East and South-East Asia. Mobile apps related to the COVID-19 pandemic continue to emerge and evolve with a wide variety of characteristics and functions. However, there is a paucity of studies evaluating such apps in this region, with most of the available studies conducted in the early days of the pandemic. Objective This study aimed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 44 publications
2
34
0
2
Order By: Relevance
“…Users also reported that they could not gather comprehensive output about patient history from the apps. These also confirm previous findings in a previous systematic review in East and South-East Asia ( 35 ). The review also found that the key feature to suppress coronavirus spread, contact tracing, was unavailable in most apps.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Users also reported that they could not gather comprehensive output about patient history from the apps. These also confirm previous findings in a previous systematic review in East and South-East Asia ( 35 ). The review also found that the key feature to suppress coronavirus spread, contact tracing, was unavailable in most apps.…”
Section: Discussionsupporting
confidence: 92%
“…Despite that, a few apps are used to educate or train patients, families, and support staff. This finding corroborates a previous review of COVID-19 apps in East and South-East Asia and highlights the primary function of COVID-19 mHealth apps in most countries in the region for dissemination purposes ( 35 ). While interactive services and targeted client communication are crucial ( 11 ), most apps were still not designed for interactive engagement with users.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A better management with special consideration must be given to patients with STDs, such as against discrimination on STDs, encourage self-testing and online medical care, offer necessary remote consultation and medical support, express delivery drugs and special medical pass when lockdown during the COVID-19 pandemic. Evidence has shown that mobile health (mHealth) in mobile apps has been used to enable health care providers to reach out to vulnerable individuals, to provide counselling, health-related education, and treatment [ 35 ]. As shown in a study by Pant Pai et al [ 36 ], an unsupervised HIV self-testing strategy using an internet-based mHealth provided counselling and treatment among patients testing positive in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 Tracing Apps (CTAs) have been considered as an (cost-)effective mitigation strategy, by informing people as soon as possible when they have been in close contact with an infected person (Ming et al, 2020;Lee et al, 2021). Nonetheless, the actual adoption and usage of mobile health apps is rather low and lagging behind its promises (Walrave et al, 2020).…”
Section: Introductionmentioning
confidence: 99%